Prediction of DCT Coefficients Considering Motion Compensation Error Distributions - Schmidt, Julia; Edler, Bernd; Ostermann, Jörn (Proceedings of Visual Communications and Image Processing (VCIP 2011), 2011)
Current video coding techniques use a Discrete Cosine Transform (DCT) to reduce spatial correlations within the motion estimation residual. Often the correlation cannot be completely eliminated leaving the transform coefficients statistically dependent. The presented paper proposes a method to predict these coefficients on a block level by using the distribution of the prediction error variance to improve coding efficiency. First experiments lead to a reduction in bit rate by 1.83% when compared to the standard JM 17.2 implementation results.<br